2014
DOI: 10.2478/s11756-014-0388-2
|View full text |Cite
|
Sign up to set email alerts
|

Shrimps of an ancient Balkan lake: Bionomy and conservation

Abstract: In order to have a comprehensive evaluation and classification of the natural biota of Lake Pamvotis, the present study aims at investigating shrimps' bionomic traits. Information on shrimps' habitat preferences, abundances, and syntopic species in relation to the physicochemical profile of the lake's water are investigated for the first time. The study was carried out on a bi-monthly base, at six littoral sites of the lake. Samples' study from different habitats and seasons revealed that the freshwater shrimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…One example concerning Palaemonidae is the study by Cartaxana (2015), who on the basis of measurements of the body parts and genetic data suggested the fusion of two Palaemon species. Similar linear distance-based morphometric studies of Palaemon antennarius in north-western Greece by Anastasiadou et al (2009Anastasiadou et al ( , 2014Anastasiadou et al ( , 2017 showed some phenotypic plasticity connected with sex and the type of habitat, although their studies were not supported by genetic analyses.…”
Section: Discussionmentioning
confidence: 79%
“…One example concerning Palaemonidae is the study by Cartaxana (2015), who on the basis of measurements of the body parts and genetic data suggested the fusion of two Palaemon species. Similar linear distance-based morphometric studies of Palaemon antennarius in north-western Greece by Anastasiadou et al (2009Anastasiadou et al ( , 2014Anastasiadou et al ( , 2017 showed some phenotypic plasticity connected with sex and the type of habitat, although their studies were not supported by genetic analyses.…”
Section: Discussionmentioning
confidence: 79%